2020
DOI: 10.1038/s41598-020-72203-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic critical behavior of the van der Waals Fe5GeTe2 crystal with near room temperature ferromagnetism

Abstract: The van der Waals ferromagnet Fe5GeTe2 has a Curie temperature TC of about 270 K, which is tunable through controlling the Fe deficiency content and can even reach above room temperature. To achieve insights into its ferromagnetic exchange that gives the high TC, the critical behavior has been investigated by measuring the magnetization in Fe5GeTe2 crystal around the ferromagnetic ordering temperature. The analysis of the measured magnetization by using various techniques harmonically reached to a set of relia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 60 publications
7
50
1
Order By: Relevance
“…The Mr can be reasonably fitted with 3D models (see Supplementary Figure 4). However, our determined β significantly deviates from the corresponding magnetic critical exponent and from the one observed in bulk-crystals β ≈ 0.346 23 . With a value of β ≈ 0.294, our results approaches the window for critical exponents of two-dimensional systems 34 , and possibly indicates a characteristic 2D behavior in ultrathin films.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…The Mr can be reasonably fitted with 3D models (see Supplementary Figure 4). However, our determined β significantly deviates from the corresponding magnetic critical exponent and from the one observed in bulk-crystals β ≈ 0.346 23 . With a value of β ≈ 0.294, our results approaches the window for critical exponents of two-dimensional systems 34 , and possibly indicates a characteristic 2D behavior in ultrathin films.…”
Section: Resultscontrasting
confidence: 89%
“…using Fe-deficient bulk crystals or micrometer-sized flakes exfoliated from them 7,[21][22][23] . The properties of Fe5GeTe2 films with exact 5:1:2 stoichiometry remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, T c can be significantly raised to about room temperature by enhancing exchange interaction while keeping the vdWs structure, 12 such as in the layered 2D Fe n GeTe 2 (n≥ 3). 13,14 This led to Fe 3 GeTe 2 with T c around 220 K, 9,15,16 Fe 4 GeTe 2 with T c = 270 K, 12 and Fe 5 GeTe 2 with T c ranging from 260 -310K, depending on the Fe content. 14,17,18 Ferromagnetic resonance (FMR) spectroscopy is an important technique to study magnetization dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 This led to Fe 3 GeTe 2 with T c around 220 K, 9,15,16 Fe 4 GeTe 2 with T c = 270 K, 12 and Fe 5 GeTe 2 with T c ranging from 260 -310K, depending on the Fe content. 14,17,18 Ferromagnetic resonance (FMR) spectroscopy is an important technique to study magnetization dynamics. 19,20 Several studies have analyzed the spin dynamics in 2D magnets by FMR, [21][22][23] which revealed their magnetocrystalline anisotropy dependence on temperature.…”
Section: Introductionmentioning
confidence: 99%